Molecular cloning, characterization and expression analysis of LoTPS2 and LoTPS4 involved in floral scent formation in oriental hybrid Lilium variety 'Siberia'. (May 2020) - Abbas, Farhat; Ke, Yanguo; Zhou, Yiwei; Ashraf, Umair; Li, Xinyue; Yu, Yunyi; Yue, Yuechong; Ahmad, Kanwar Waqas; Yu, Rangcai; Fan, Yanping
Abstract : Lilies are a commercially significant cut flower worldwide due not only to their elegant shape but also to their appealing scent. Among Lilium varieties, Lilium 'Siberia' is a cultivar that is prominent and highly favored by consumers due to its snowy white color and strong floral scent. Here, two terpene synthase genes ( LoTPS2 and LoTPS4 ) that are responsible for floral scent production in Lilium 'Siberia' were cloned and functionally characterized. Recombinant LoTPS2 specifically catalyzed the formation of ( E, E )-α-farnesene from FPP. Recombinant LoTPS4 is a multiproduct enzyme that produces D-limonene and β-myrcene as major volatile compounds and β-phellandrene, (+)-4-carene and 3-carene as minor products from GPP. Furthermore, LoTPS4 generates trans-α-bergamotene as a major product and di-epi-α-cedrene, α-cubebene and ( E )-β-farnesene as minor compounds from FPP. Subcellular localization analysis using GFP fusion constructs revealed that LoTPS2 was localized in the cytosol, whereas LoTPS4 was localized in plastids. Real-time PCR analysis showed that LoTPS2 was highly expressed in the petals and sepals of the flower, while LoTPS4 was highly expressed in the filament of the flower. Moreover, mechanical wounding of flowers revealed that LoTPS2 showed a strong response to wounding via a rapid increase in its mRNA transcript level. Our results will assist scientists in exploring the molecular mechanisms of terpene biosynthesis in this species and will provide new insight into the biotechnological modification of the floral bouquet in Lilium . Graphical abstract: Image 1 Highlights: Heterologous expression suggests that LoTPS2 functions as an ( E, E )-α-farnesene synthase. LoTPS4 produces a mixture of monoterpenes and sesquiterpenes from GPP and FPP, respectively. LoTPS2 is highly expressed in flower petals and sepals and responds to injury. LoTPS2 localizes to the cytosol, while LoTPS4 localizes to the plastids.